2020
DOI: 10.1093/ptj/pzaa007
|View full text |Cite
|
Sign up to set email alerts
|

The Sensor Technology and Rehabilitative Timing (START) Protocol: A Randomized Controlled Trial for the Rehabilitation of Mild Traumatic Brain Injury

Abstract: Background Clinical practice for rehabilitation after mild traumatic brain injury (mTBI) is variable, and guidance on when to initiate physical therapy is lacking. Wearable sensor technology may aid clinical assessment, performance monitoring, and exercise adherence, potentially improving rehabilitation outcomes during unsupervised home exercise programs. Objective The objectives of this study were to: (1) determine whether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Data collection details for each study have been previously reported. 8,40,41 Common demographic details that were collected included participant age (yrs), sex, height (m), mass (kg), and body mass index (BMI). Symptom severity and the total number of symptoms as derived by the second Sports Concussion Assessment Tool (SCAT-2) were also collected during each study.…”
Section: Data Collectionmentioning
confidence: 99%
“…Data collection details for each study have been previously reported. 8,40,41 Common demographic details that were collected included participant age (yrs), sex, height (m), mass (kg), and body mass index (BMI). Symptom severity and the total number of symptoms as derived by the second Sports Concussion Assessment Tool (SCAT-2) were also collected during each study.…”
Section: Data Collectionmentioning
confidence: 99%
“…In recent years, small sensors that can be attached to the body to acquire biological data, called "wearable devices," have been used extensively worldwide [1] . Wearable devices are used in clinical research and many medical and healthcare elds including neurology [2] , cardiology [3] , respiratory medicine [4] , and rehabilitation medicine [5] . In the eld of neurology, for example, applications that collect data from accelerometers in mobile devices have been used to quantify postural instability in Parkinson's disease [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, small sensors that can be attached to the body to acquire biological data, called "wearable devices," have been used extensively worldwide [1] . Wearable devices are used in clinical research and many medical and healthcare fields including neurology [2] , cardiology [3] , respiratory medicine [4] , and rehabilitation medicine [5] . In the field of neurology, for example, applications that collect data from accelerometers in mobile devices have been used to quantify postural instability in Parkinson's disease [6] .…”
Section: Introductionmentioning
confidence: 99%